The impacts of digital value chain embeddedness on trade-related carbon emissions intensity - Lyu, Yanfang; Xiang, Yun; Wang, Dong (Frontiers in Environmental Science, 2024)
Dear editor and reviewer, Thank you very much for your insightful and constructive comments. These suggestions help to improve academic rigor of our study. The revised documents with changes marked in red have been uploaded, and we'd like to show the point-by-point response as follows:Comment 7: There is room for improvement in the description of the results in the abstract, which can increase the support of quantitative data. Response 7: Thank you very much for your suggestion. We have followed your advice by increasing some quantitative descriptions of the results. Some revisions are shown below for your inspection, details can be seen in lines 20-22, lines 24-25, lines 28-30."Research findings indicate that there is an inverted U-shaped relationship between digital domestic value chain embeddedness and carbon emissions intensity embodied in domestic trade, only when digitalization reaches the threshold level that is about 0.88, the effects on carbon emissions intensity become negative.""the thresholds of digitalization are about 0.1 and 0.3 as for the category of import trade, whereas the thresholds are about 0.03 and 0.21 as for the category of export trade.""Compared with developed countries, developing countries lag behind in entering the downward stage of the inverted U-shaped curve, thereby gaining environmental benefits from digital value chain embeddedness.